Development and initial cohort validation of the Arthritis Research UK Musculoskeletal Health Questionnaire (MSK-HQ) for use across musculoskeletal care pathways. Issue 8 (5th August 2016) - Hill, Jonathan C; Kang, Sujin; Benedetto, Elena; Myers, Helen; Blackburn, Steven; Smith, Stephanie; Dunn, Kate M; Hay, Elaine; Rees, Jonathan; Beard, David; Glyn-Jones, Sion; Barker, Karen; et al.
Abstract : Objectives: Current musculoskeletal outcome tools are fragmented across different healthcare settings and conditions. Our objectives were to develop and validate a single musculoskeletal outcome measure for use throughout the pathway and patients with different musculoskeletal conditions: the Arthritis Research UK Musculoskeletal Health Questionnaire (MSK-HQ). Setting: A consensus workshop with stakeholders from across the musculoskeletal community, workshops and individual interviews with a broad mix of musculoskeletal patients identified and prioritised outcomes for MSK-HQ inclusion. Initial psychometric validation was conducted in four cohorts from community physiotherapy, and secondary care orthopaedic hip, knee and shoulder clinics. Participants: Stakeholders (n=29) included primary care, physiotherapy, orthopaedic and rheumatology patients (n=8); general practitioners, physiotherapists, orthopaedists, rheumatologists and pain specialists (n=7), patient and professional national body representatives (n=10), and researchers (n=4). The four validation cohorts included 570 participants (n=210 physiotherapy, n=150 hip, n=150 knee, n=60 shoulder patients). Outcome measures: Outcomes included the MSK-HQ's acceptability, feasibility, comprehension, readability and responder burden. The validation cohort outcomes were the MSK-HQ's completion rate, test–retest reliability and convergent validity with reference standards (EQ-5D-5L, Oxford Hip, Knee, Shoulder Scores, and the Keele MSK-PROM). Results: Musculoskeletal domains prioritised were pain severity, physical function, work interference, social interference, sleep, fatigue, emotional health, physical activity, independence, understanding, confidence to self-manage and overall impact. Patients reported MSK-HQ items to be 'highly relevant' and 'easy to understand'. Completion rates were high (94.2%), with scores normally distributed, and no floor/ceiling effects. Test–retest reliability was excellent, and convergent validity was strong (correlations 0.81–0.88). Conclusions: A new musculoskeletal outcome measure has been developed through a coproduction process with patients to capture prioritised outcomes for use throughout the pathway and with different musculoskeletal conditions. Four validation cohorts found that the MSK-HQ had high completion rates, excellent test–retest reliability and strong convergent validity with reference standards. Further validation studies are ongoing, including a cohort with rheumatoid/inflammatory arthritis.